KEMAMPUAN MENULIS CERPEN BERBANTUAN MEDIA GAMBAR FASE F SMAN 2 SUNGAI TARAB - Holida Fahrani; Dina Ramadhanti; Trisna Helda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the short story writing skills of phase F students at SMAN 2 Sungai Tarab assisted by image media in terms of plot, characterization, and setting. This research used a quantitative approach with a descriptive method. The population of this study was all phase F students totaling 71 students, and the sample was 23 students selected using purposive sampling technique. The research instrument was a performance test in the form of a short story writing task based on the provided images. The data were analyzed using percentage techniques and converted into a ten-scale assessment. The results showed that the students’ short story writing skills assisted by image media were in the more than adequate qualification. The ability to develop plot was in the good category, characterization was in the adequate category, and setting was in the adequate category. The use of image media helps students develop ideas and organize story elements more systematically. Therefore, image media can be used as an alternative learning medium in improving students’ short story writing skills.